Kompetensi Pedagogik Guru PAI-BP SDN 14 Kelurahan Atts Kota Bukittinggi - Nadianto, Pariyal; Yenti, Endri (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The purpose of this study was to know the pedagogical competencies of Islamic Religious Education-BP teachers in elementary school 14 ATTS Bukittinggi. The background underlying this study is that, due to the underutilization of pedagogical skills by teachers, students’ overall learning outcomes do not improve. As for the method used in this study it was qualitative descriptive, with the data collection methods being observation, interview, and documentation. The findings of the study showed that Islamic Religious Education teachers in SDN 14 ATTS Bukittinggi already possess strong pedagogical competencies, and learning is conducted very well.